Analisis Asupan Zat Gizi Terhadap Status Gizi Balita - Lina Dewi Anggraeni; Yohana Riang Toby; Sada Rasmada (Faletehan Health Journal, 2021)
Nutritional status is a depiction of food security needed by the body. The impacts due to the incidence of malnutrition and overnutrition experienced by children under five years are worrying. The purpose of this study was to determine the factors associated with the nutritional status of under five year children in Pustu Oebufu, Oebobo Sub-District Kupang City in February 2018. The research type used was observational analytic with the cross-sectional design approach. The population were children under five years who were in the service coverage of Oebufu Pustu work area. The sampling technique was purposive and the sample size was 136 mothers who had a child under five. The study found 73.5% of under-five children had normal nutritional status. The statistical test results showed that there is a relationship between education (p=0.015), knowledge (p=0.000), and food supply such as energy intake (p=0.000), protein (p=0.000), fat (p=0.000), carbohydrate (p=0.000), vitamin A (p=0.000), vitamin C (p=0.000), calcium (p=0.002), iron (p=0.000) and zink (p=0.000) with nutritional status (p-value < 0.05). Parent involvement, especially mothers, is closely related to the nutritional status of under five year children. Mothers should have good knowledge of nutrient intake for children under five.